1973
DOI: 10.1002/1097-0142(197307)32:1<89::aid-cncr2820320112>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

An oncornavirus isolated from human cancer cell line

Abstract: A virus has been isolated from a clone of continuous cell line that was derived from human cancer tissue (HEp‐2 cells). The clone of HEp‐2 cells retains human Karyotype and has no heterogeneous contamination. Injection of the cells and the virus into mice of C3H/Sn, C3H/H2P, BaLB/c lines and into newborn hamsters did not produce tumors in animals. Intracellular virus possesses morphological characteristics of oncornaviruses type A and B; extracellular virus has the properties of oncornaviruses type B. The viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…All other retroviruses tested in our laboratory up to now appeared to suppress the lymphocyte mitogen response (It, DE~EI~ et al, unpublished). Among the viruses tested were the bovine leukemia virus and two other type D viruses isolated from human cell lines, the HeLa-virus (2) and the HEp-2 virus (20). On the other hand, using a macrophage function test, CIA~ClOLO et al (6) found a number of viruses, including the feline leukemia virus (FeLV), the mouse mammary tumor virus and the Gibbon ape leukemia virus, which did not inhibit murine macrophages.…”
Section: Interspecies Reactivity O/pme V-induced Suppression O/lymphomentioning
confidence: 99%
See 2 more Smart Citations
“…All other retroviruses tested in our laboratory up to now appeared to suppress the lymphocyte mitogen response (It, DE~EI~ et al, unpublished). Among the viruses tested were the bovine leukemia virus and two other type D viruses isolated from human cell lines, the HeLa-virus (2) and the HEp-2 virus (20). On the other hand, using a macrophage function test, CIA~ClOLO et al (6) found a number of viruses, including the feline leukemia virus (FeLV), the mouse mammary tumor virus and the Gibbon ape leukemia virus, which did not inhibit murine macrophages.…”
Section: Interspecies Reactivity O/pme V-induced Suppression O/lymphomentioning
confidence: 99%
“…After the isolation of the Mason-Pfizer monkey virus (MPMV) from a female rhesus monkey (9), morphologically similar viruses have been isolated from several continuous human cell lines (2,18,20). Based on electron microscopic and biochemical criteria these viruses have been classified as type D retroviruses (for review see 16,32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of isolated reports have appeared over the last 15 years describing serological reactivity of human sera to type D virus antigens (22,34,35,44,45). In addition, a number of established human cell lines producing type D retroviruses have been described (11,16,24,25,37,47 cell line-derived type D isolates have been physically mapped with restriction endonucleases, and at least two of them have been molecularly cloned and sequenced. One cloned isolate was closely related to SRV-1 (30), and the other was very similar to the squirrel monkey retrovirus (36).…”
mentioning
confidence: 99%
“…MPMVp26 vs SMRV '%p36,RPMl 8226V,SMRV and Several laboratories demonstrated D-type virus particles in various established human cell lines (Bauer et al, 1974;Gelderblom et al, 1974;Ilyin et al, 1973;Zhdanov et al, 1973). Most of these virus particles were detected in cell lines exhibiting HeLa cell characteristics (Nelson-Rees et al, 1971) and the isolated viruses (designated also as "HeLa virus") were indistinguishable morphologically, biologically, and biochemically from Mason-Pfizer monkey virus (MPMV) (Bauer et al, 1974;Priori et al, 1976).…”
mentioning
confidence: 99%